18F-Sodium Fluoride (18F-NaF) for Imaging Microcalcification Activity in the Cardiovascular System. Issue 7 (July 2020) - Tzolos, Evangelos; Dweck, Marc R.
Abstract : Accumulating preclinical and clinical evidence suggests that calcification is one of the body's primary responses to injury and a key pathological feature of cardiovascular disease. Calcification activity can now be imaged using 18 F-sodium fluoride ( 18 F-NaF) positron emission tomography (PET) in combination with either computed tomography or magnetic resonance. These techniques allow visualization of calcification activity and, therefore, provide different information to the established macroscopic calcium imaged with computed tomography. Indeed, 18 F-NaF PET has been used to investigate a wide range of valvular conditions, including aortic stenosis, mitral annular calcification, and bioprosthetic valve disease, as well as vascular conditions, including abdominal aortic aneurysm disease, coronary, and carotid atherosclerosis, peripheral vascular disease, and erectile dysfunction. In this brief review, we will focus on how 18 F-NaF PET has improved our pathophysiological understanding of cardiovascular calcification and how it can be used as a marker of vascular calcification, providing a useful tool that can be utilized in clinical trials investigating the prediction of both disease progression and clinical events. Finally, we will discuss how 18 F-NaF might be employed clinically to improve patient assessment and to guide decision-making.